ANALISIS FINANCIAL LEVERAGE, LIKUIDITAS DAN PROFITABILITAS TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN PERBANKAN - Viola Syukrina E Janrosl; Y Yuliadi (KRISNA: Kumpulan Riset Akuntansi, 2019)
This study aims to analyze financial leverage, liquidity and profitability of financial fraud statements in banking companies. Financial statement fraud (fraudulent financial statements) as an intentional or unintentional act or act, which causes financial statements to be materially misleading. The population used in this study is a banking company, while the sample used in this study is the financial statements of banking companies listed on the Indonesia Stock Exchange from 2015 - 2017. This research is a causative research, namely research designed to measure the relationship between variables research, or analyze the influence of a variable on other variables. Research design is a framework used in a study. The results of this research financial leverage have a significant effect on financial statement fraud. Liquidity has a significant effect on financial statement fraud. Profitability has no significant effect on financial statement fraud. Simultaneously financial leverage, liquidity and profitability together have a significant effect on financial statement fraud.